New genera and species of tortricid moths from Chile and Argentina (Lepidoptera: Tortricidae) - Brown, John W. (Zootaxa, 2024)
Seven new genera in the tortricid subtribe Euliina (Cochylini) are described and illustrated from Chile and Argentina: Argentiliana, new genus, and its type species A. basipallida, new species; Terifrona, new genus, and its type species T. fronteria, new species; Transtilliana, new genus, and its type species T. biloba, new species; Vargasia, new genus, and its type species V. karsholti, new species; Hamiamia, new genus, and its type species H. trancasiana (Razowski & Pelz, 2010), new combination; Endemulia, new genus, and its type species E. urrai, new species; and Silenoides, new genus, and its type species, S. divergens, new species. The following new species are also described and illustrated: Varifula geomops, new species; Proeulia hasta, new species; Proeulia razowskii, new species; Strophotina samara, new species; Gnatheulia flava, new species; Paratepa argentinana, new species; Galomecalpa decolorana, new species; and Archipimima clarkei, new species. All but Archipimima are assigned to Euliina; Archipimima is assigned to Atteriini. Cnephasia clisias Meyrick and C. dryoglypta Meyrick are transferred to Paratepa, resulting in Paratepa clisias (Meyrick, 1912), new combination, and P. dryoglypta (Meyrick, 1913), new combination. The adult and female genitalia of Chapoania dentigera Razowski are illustrated for the first time. A preliminary comparison of the Argentine and Chilean tortricid faunas is provided.